2018
DOI: 10.1038/s41598-018-22965-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high pressure on the electrical resistivity and dielectric properties of nanocrystalline SnO 2

Abstract: The electrical transport and structural properties of tin oxide nanoparticles under compression have been studied by in situ impedance measurements and synchrotron X-ray diffraction (XRD) up to 27.9 GPa. It was found that the conduction of SnO2 can be improved significantly with compression. Abnormal variations in resistivity, relaxation frequency, and relative permittivity were observed at approximately 12.3 and 25.0 GPa, which can be attributed to pressure-induced tetragonal- orthorhombic-cubic structural tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…Each Sn atom is centered around a cage of a slightly distorted oxygen octahedron. The expected zone center optical phonon modes are A 1g + A 2g + B 1g + B 2g + E g + A 2u + 2B 1u + 3E u . Out of these, four phonons (A 2u + 3E u ) are infrared-active, the other four (A 1g + B 1g + B 2g + E g ) are Raman-active modes, and the remaining ones (A 2g + 2B 1u ) are optically silent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each Sn atom is centered around a cage of a slightly distorted oxygen octahedron. The expected zone center optical phonon modes are A 1g + A 2g + B 1g + B 2g + E g + A 2u + 2B 1u + 3E u . Out of these, four phonons (A 2u + 3E u ) are infrared-active, the other four (A 1g + B 1g + B 2g + E g ) are Raman-active modes, and the remaining ones (A 2g + 2B 1u ) are optically silent.…”
Section: Resultsmentioning
confidence: 99%
“…Upon decrease in size of SnO 2 NPs, disorder in the outer shell of NPs increases and affects the phonon spectra . Remarkably, NPs’ phase stability is size-dependent, and its properties are argued to be strongly influenced by defects and oxygen stoichiometry. Furthermore, as pressure is a clean parameter, Raman study of these nanomaterials under compression could provide insight into their structural and thermal behavior. Inference on thermal behavior can be obtained from the mode Gruneisen parameters that directly contribute to the thermal expansion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance the pressure -resistance relationship of a pressure transducer could be attributed to decrease in thickness and accordingly the porosity of the sensing materials when pressure is applied. (Shen et al, 2018). In addition, the conductivity in metal oxides is considered to be through thermally assisted hopping transitions between spatially separated sites/particles.…”
Section: Morphological Observationmentioning
confidence: 99%
“…It was concluded that compression increased the dielectric constant and dissipation factor of all the composites. Shen et al [ 9 ] conducted a study on dielectric properties of SnO 2 under high pressure and found that the dielectric constant and loss tangent decreased with increasing frequency. Authors of [ 10 ] studied the effects of mechanical stresses on polymeric materials and concluded that all the critical phenomena, including a decrease of dielectric strength, electrical tree growth, accumulated damage, space charge accumulation, etc., in insulating polymer materials are significantly influenced by internal (residual) and external mechanical stresses.…”
Section: Introductionmentioning
confidence: 99%